Hubungan Self Efficacy Ibu Hamil Trimester III dengan Kepatuhan Kunjungan Antenatal Care - Mutmainnah Mutmainnah; Nila Widya Keswara (Indo Green Journal, 2026)
Consistent Antenatal Careb visits can reduce morbidity during pregnancy, childbirth, and the postpartum period. Self-efficacy is a key internal actor influencing a pregnant woman's motivation to adhere to established health standards. This study aims to analyze the relationship between the self-efficacy of third-trimester pregnant women and their adherence to Antenaatal Care. This is a quantitative study employing a cross-sectional approach. The population consisted of all 60 third-trimester pregnant women at the research site, with the sample selected using a total sampling technique. Data were collected through questionnaire and observation sheets, then analyzed using the Chi-Square test. The result showed that 80% of respondent were categorized as adherent, and 90.6% of respondents with high self-efficacy demonstrated good adherence. Statistical analysis yielded a p-value of 0.000 (p < 0.05), indicating a significant relationship between self-efficacy and adherence to Antenatal Carem visits. In conclusion, higher self-efficacy in third-trimester pregnant women is associated with better adherence to antenatal care visit.